REGULATION OF LEGAL AUTHORITY OF INDIVIDUAL COMPANY FOUNDERS WHO ARE NOT YET 18 YEARS OLD FROM THE PERSPECTIVE OF THE LAW ON THE OFFICE OF A NOTARY - Dita Anggraini Sholikhah; Hanif Nur Widhiyanti; Faizin Sulistio (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this article is to analyze the regulation of the legal authority of individual companies that are not yet 18 years old from the perspective of the law on notary positions by reviewing Government Regulation Number 8 of 2021 concerning Authorized Capital of Companies and Registration of Establishment, Changes and Dissolution of Companies that Meet the Criteria for Micro Businesses. and Minor, the Notary Position Law, the Civil Code, the Marriage Law, and also the Child Protection Law. There is a difference in these regulations, namely determining a person's adult age and legal capacity. The research method used is normative juridical using primary legal materials which are analyzed using a statutory approach and a conceptual approach. The research results show thatThere is disharmony in the regulation of the legal authority of founders of individual companies between PP Number 8 of 2021 and UUJN and Circular Letter of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 4/SE/I/2015. The disharmony in the regulation of the legal authority of the founder of an individual company means that the founder of an individual company cannot represent his company to carry out material and civil legal actions that require an authentic deed from a notary/PPAT.